21st Century Challenges of Social Work´s Accountability in Post-Soviet Estonian Rural Local Governments (London Journal of Research In Humanities and Social Sciences, 2024)
Contemporary European social work is based on the principles of collective responsibility, human rights, and social justice. The IFSW (International Federation of Social Workers) declared that social work was, and always will be, a human rights occupation. Before for the described outcome of social work, the social work has required the aims, strategies and the methods of implementation. The preparation and adoption of the Social Care (Welfare) Act in 1995 followed the general principles of the corresponding law from 1925, in that the responsibility for organizing social welfare fell to local government. Thus, at the end of the 20th century, the main public social welfare organizer in Estonia is the local government and the local governments are part of the European Union since the year 2004.Following an accountable approach, this research has aimed to explore developed accountability of social welfare in the rural local government.The utilized methodology has been the collective case study (Mills 2010). I followed the information-oriented selection: the cases of maximum variation by size and location (Luck, Jackson & Usher 2006). Triangulation has been used as a procedure for acquiring data. Further analysis was conducted by using a taxonomic approach (Ragin 2011).
Keywords: accountability; Human Rights; case study; human services; rural social work; access to services